2020
DOI: 10.1136/bmjpo-2020-000662
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zinc as adjunctive pneumonia treatment in children aged 2 to 60 months in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: BackgroundDespite advances in vaccination and case management, pneumonia remains the single largest contributor to early child mortality worldwide. Zinc has immune-enhancing properties, but its role in adjunctive treatment of pneumonia in low-income and middle-income countries (LMICs) is controversial and research still active.MethodsSystematic review and meta-analysis of randomised controlled trials of zinc and placebo in pneumonia in children aged 2 to 60 months in LMICs. Databases included MEDLINE, the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Zinc is required for a wide variety of immune functions ( 299 ) and those deficient in zinc, particularly children, are prone to increased diarrheal and respiratory infections. Zinc supplementation has been shown to significantly reduce the frequency and severity of both infections in children ( 300 ), although such findings are not universal [e.g., Howie et al ( 301 )], and a recent systematic review and meta-analysis found no evidence that adjunctive zinc treatment improves recovery from pneumonia in children in LMICs ( 302 ). Similar to vitamin C, zinc supplementation has also been suggested as a potential remedy for the treatment of the common cold (rhinovirus infection); a meta-analysis of 3 trials reporting on 199 patients supports a faster recovery time ( 303 ), although the small sample size ( n = 199) of included studies warrants caution.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is required for a wide variety of immune functions ( 299 ) and those deficient in zinc, particularly children, are prone to increased diarrheal and respiratory infections. Zinc supplementation has been shown to significantly reduce the frequency and severity of both infections in children ( 300 ), although such findings are not universal [e.g., Howie et al ( 301 )], and a recent systematic review and meta-analysis found no evidence that adjunctive zinc treatment improves recovery from pneumonia in children in LMICs ( 302 ). Similar to vitamin C, zinc supplementation has also been suggested as a potential remedy for the treatment of the common cold (rhinovirus infection); a meta-analysis of 3 trials reporting on 199 patients supports a faster recovery time ( 303 ), although the small sample size ( n = 199) of included studies warrants caution.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 studies were identified, including seven SRs and 25 RCTs. All SRs studied nutritional supplements as an adjunct treatment of pneumonia, with two evaluating zinc [ 17 , 18 ] and one each evaluating vitamin A [ 20 ], vitamin D [ 23 ], and vitamin C [ 22 ]. Two of these SRs examined the effectiveness of multiple adjunct therapies (zinc and vitamin A) [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Howie et al . 320 ) and a recent systematic review and meta-analysis found no evidence that adjunctive zinc treatment improves recovery from pneumonia in children in low- and middle-income countries 321 . Similar to vitamin C, zinc supplementation has also been suggested as a potential remedy for the treatment of the common cold (rhinovirus infection); a meta-analysis of 3 trials reporting on 199 patients supports a faster recovery time 322 although the small sample size (N=199) of included studies warrants caution.…”
Section: Zincmentioning
confidence: 98%